2006
DOI: 10.1038/sj.leu.2404118
|View full text |Cite
|
Sign up to set email alerts
|

Relapse of acute promyelocytic leukemia with PML-RARα mutant subclones independent of proximate all-trans retinoic acid selection pressure

Abstract: Relapse of acute promyelocytic leukemia (APL) following alltrans retinoic acid (ATRA) therapy has been associated with the acquisition of mutations in the high-affinity ATRA binding site in PML-RARa, but little information is available about the selection dynamics of the mutation-harboring subclones. In this study, 6/18 patients treated with sequential ATRA and chemotherapy on protocol INT0129 relapsed with complete replacement of the nonmutant pretreatment APL cell population by a PML-RARa mutant subclone. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 33 publications
(28 reference statements)
1
26
0
Order By: Relevance
“…However, in patients, ATRA does not lead to complete remission without accompanying chemotherapy, 16,17 and some patients may develop resistance. 18 Valproic acid (VPA) belongs to the class I HDACi, which has been widely used as an antiepileptic drug. VPA induces growth arrest, differentiation and apoptosis in many leukemic cell lines, as well as in fresh leukemic blasts.…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients, ATRA does not lead to complete remission without accompanying chemotherapy, 16,17 and some patients may develop resistance. 18 Valproic acid (VPA) belongs to the class I HDACi, which has been widely used as an antiepileptic drug. VPA induces growth arrest, differentiation and apoptosis in many leukemic cell lines, as well as in fresh leukemic blasts.…”
Section: Introductionmentioning
confidence: 99%
“…In four of six patients from protocol E2491 who relapsed with LBD mutations, the APL clone harboring the mutation emerged and replaced the previously predominant wild-type PML-RARa APL cell population long after the last treatment with ATRA. 3 These observations suggested that LBD mutation-harboring clones might selectively acquire ATRA-independent mechanism(s) of increased APL cell proliferation/survival competitiveness, and that this mechanism(s) might be favored in late relapse patients. In a collaborative effort to further explore this possibility, samples from previously reported late relapse patients, that is, relapse after 44 years, 5 were not available; however, eight relapse samples from patients with a relatively long interval to first relapse (median, 1015 days after treatment on French-Belgian-Swiss APL group protocol, APL2000, or off-protocol in a similar manner), 2 were available and were analyzed (Table 1).…”
mentioning
confidence: 99%
“…In patient 6, second relapse occurred despite the use of arsenic trioxide consolidation therapy, suggesting that targeting the PML region of PML-RARa by arsenic trioxide, 1 which would include the truncation mutant clone, was insufficient to prevent disease recurrence. Similarly, all three alternatively reported APL patients who relapsed with LBD deletion mutations on protocols E2491 and C9710 succumbed to their disease during the protocol follow-up period (one on ATRA, two off ATRA; see Gallagher et al 3 and Gallagher et al 4 and manuscript in preparation). Together, these observations suggest that the infrequent patients who relapse with deletion or insertion/truncation mutations in PML-RARa are at increased risk of poor clinical outcome.…”
mentioning
confidence: 99%
See 2 more Smart Citations